Pengalaman Perawat dalam Melakukan Pengkajian Pasien Baru Di Satu Rumah Sakit Swasta Di Indonesia Bagian Barat [Experience Of Nurses in Conducting Assessment on New Patients in One Of The Private Hospitals in West Indonesia] - Grace Ivo; Marisa Manik; Oberlin Simamora (Universitas Pelita Harapan, 2018)
The nurse carries out an assessment (history) of the patient when the patient is admitted to the hospital about the complaint or problem. Accurate assessment, complete according to reality, and correctness of data is very important for the next step in providing nursing care according to individual responses. Researchers still find studies that are not carried out accurately and completely, especially in the inpatient room where researchers practiced. The nurse does not conduct a direct study of the patient but has filled in the new patient assessment documentation. The purpose of this study was to determine the experience of nurses in conducting a study of new patients in the inpatient room at a Private Hospital in Western Indonesia. This study uses phenomenological qualitative research methods by collecting data through interviews and double checks (on patients and assessment documents). The number of samples studied was six nurses. This research was conducted in October-November 2017. The results of this study indicate that there were five themes related to the experience of nurses in conducting a new patient assessment. The five themes are the experience of carrying out the nursing process, conducting new patient assessments, as well as the driving factors in carrying out the assessment, the benefits obtained and obstacles in conducting the assessment. The number of categories from the five themes is 16 categories. The patient assessment sheet was almost completely filled by the nurses except that the body weight and height were still not all filled, which amounted to 66.66% of the total documentation sample conducted by the six respondents. It can be concluded that the assessment conducted by nurses in the inpatient room in one Western Indonesian Private Hospital can be said to be complete but inaccurate where not all studies were carried out directly to patients but were filled in the assessment sheet.BAHASA INDONESIA Perawat melakukan pengkajian (anamnesis) terhadap pasien ketika pasien masuk rumah sakit mengenai keluhan atau masalahnya. Pengkajian yang akurat, lengkap sesuai kenyataan, dan kebenaran data sangat penting untuk langkah selanjutnya dalam memberikan asuhan keperawatan sesuai respon individu (Muttaqin, 2008). Peneliti masih menemukan pengkajian yang tidak dilakukan dengan akurat dan lengkap khususnya di ruang Rawat tempat peneliti melakukan praktik. Perawat tidak melakukan pengkajian langsung kepada pasien namun telah melakukan pengisian dokumentasi pengkajian pasien baru. Tujuan penelitian ini adalah untuk mengetahui pengalaman perawat dalam melakukan pengkajian pasien baru di ruang Rawat di Satu Rumah Sakit Swasta di Indonesia Bagian Barat. Penelitian ini menggunakan metode penelitian kualitatif fenomenologi dengan pengumpulan data melalui wawancara dan double check (terhadap pasien dan dokumen pengkajian). Jumlah sampel yang diteliti adalah enam perawat. Penelitian ini telah dilakukan pada bulan OktoberNovember 2017. Hasil penelitian ini menunjukan bahwa terdapat lima tema terkait pengalaman perawat dalam melakukan pengkajian pasien baru. Lima tema tersebut yaitu pengalaman melakukan proses keperawatan, melakukan pengkajian pasien baru, serta faktor pendorong dalam melakukan pengkajian, manfaat yang diperoleh dan hambatan dalam melakukan pengkajian. Jumlah kategori dari lima tema tersebut yaitu 16 kategori. Lembar pengkajian pasien hampir semua terisi lengkap oleh perawat kecuali berat badan dan tinggi badan masih belum semua terisi yaitu berjumlah 66,66% dari total keseluruhan sampel dokumentasi yang dilakukan oleh keenam responden. Hal ini dapat disimpulkan bahwa pengkajian yang dilakukan perawat di ruang Rawat di Satu Rumah Sakit Swasta Indonesia Bagian Barat dapat dikatakan lengkap namun tidak akurat dimana tidak semua pengkajian dilakukan langsung kepada pasien namun sudah terisi di lembar pengkajian